ANALISIS MUTU ES KRIM KACANG HIJAU (Phaseolus radiatus L) DAN SUSU SAPI SEGAR - Syaiful Umela (Jurnal Technopreneur (JTech), 2016)
Milk is one very important farm products as compared with other beverage ingredients, milk is a drink that is close to perfection. Milk contains nutritionally complete, ie; lactose, vitamins and minerals that our bodies need. In addition it contains glycerol fatty acid is more easily digested by the body. As a source of animal protein is very good for making milk is not easy to be replaced by other foods, especially for vulnerable groups such as infant nutrition, the elderly and pregnant or lactating women.This study aims to determine the level of preference, the melting power, protein content, total sugars and to determine the nutritional composition of the ice cream produced. The method used in this study is completely randomized design (CRD). The data were obtained and analyzed through organoleptic and proximate analysis.The results showed that the level of preference panelists for the best formulation is E2 with a value that is a sense of (4.0), aroma (3.7), texture (3.2) and colors (3.2). Results of the quality of the ice cream is melting power in all 3 treatment is in the range from 3.35 to 5.77 (m), protein content and high sugar content is E3. Based on the results of this study concluded that the overall A level of 3 treatments of ice cream are on a scale from 2.8 to 4.0 or in the standard up to the level of love. The best treatment resulting from the treatment of E2.